The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/pep2.24304
|View full text |Cite
|
Sign up to set email alerts
|

Thermally‐controlled spherical peptide gel architectures prepared using the pH switch method

Abstract: Self-assembling nanostructured peptide gels are promising materials for sensing, drug delivery, and energy harvesting. Of particular interest are short diphenylalanine (FF) peptides modified with 9-fluorenylmethyloxycarbonyl (Fmoc), which promotes the association of the peptide building blocks. Fmoc-FF gels generally form fibrous networks and while other structures have been demonstrated, further control of the gelation and resulting ordered three-dimensional structures potentially offers new possibilities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…18−21 For example, Huang et al and Almohammed et al demonstrated that it was possible to achieve distinct microstructures comprising completely different morphologies in materials produced from the same gelators by changes in temperature. 15,22,23 This was built upon by Chen et al and Dudukovic et al, who both demonstrated that microstructure morphology could be altered by varying solvent ratios within a solvent-switch gelation trigger (Figure 1a). 6,16 These studies support the aforementioned key idea that gelation within this class of materials is affected by a vast range of variables.…”
Section: ■ Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…18−21 For example, Huang et al and Almohammed et al demonstrated that it was possible to achieve distinct microstructures comprising completely different morphologies in materials produced from the same gelators by changes in temperature. 15,22,23 This was built upon by Chen et al and Dudukovic et al, who both demonstrated that microstructure morphology could be altered by varying solvent ratios within a solvent-switch gelation trigger (Figure 1a). 6,16 These studies support the aforementioned key idea that gelation within this class of materials is affected by a vast range of variables.…”
Section: ■ Introductionmentioning
confidence: 83%
“…Changing the building blocks from which the gels are formed results in a different material. Potentially less intuitive is the ability to form materials from the same gelator through altering the preparation process, leading to gels presenting distinct mechanical, or other, properties. , It has been demonstrated that different gelation triggers as well as modifications to or variations within the same trigger can all lead to distinct materials being produced from the same starting gelators. ,, , Often this is due to subtle changes to the underlying solid-like gelator network and the microstructure it presents. For example, Huang et al and Almohammed et al demonstrated that it was possible to achieve distinct microstructures comprising completely different morphologies in materials produced from the same gelators by changes in temperature. ,, This was built upon by Chen et al and Dudukovic et al, who both demonstrated that microstructure morphology could be altered by varying solvent ratios within a solvent-switch gelation trigger (Figure a). , These studies support the aforementioned key idea that gelation within this class of materials is affected by a vast range of variables.…”
Section: Introductionmentioning
confidence: 99%